2010
DOI: 10.1007/s10880-010-9205-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms and Quality of Life in Patients Affected by Epidermolysis Bullosa

Abstract: The aim of our study was to provide a psychosocial and psychiatric evaluation of patients with epidermolysis bullosa (EB; a rare genetic disorder characterized by skin fragility), to assess psychological status, ascertain the presence of any psychiatric disorders and understand the impact of EB on quality of life. Twenty-five patients were assessed using a case record form and several standardized instruments. In 82% of patients, EB had a negative impact on quality of life and 80% of patients experienced psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 13 publications
2
55
1
2
Order By: Relevance
“…In the Dutch QOLEB significant differences were seen on the functioning and overall scale, but not on the emotions scale, suggesting one of 3 explanations: either that the mental burden of EB is similar in milder and more severe subtypes, that patients with more severe EB subtypes have acquired emotional resilience due to the severe impact of living with EB, or that the QOLEB is not appropriate to distinguish between emotions. Such decreased prevalence of emotional burden is also seen with results from a study by Margari et al (13), who found that 80% of EB patients experienced sub-threshold psychiatric symptoms, in particular depression, anxiety, and behaviour disturbances, but that there was no close correlation between these symptoms and the clinical severity of EB (13). Emotional resilience was not explored by Margari et al (13) but has been proposed by Frew et al (3) to explain the lack of consistent quantitative data regarding emotional burden in EB.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In the Dutch QOLEB significant differences were seen on the functioning and overall scale, but not on the emotions scale, suggesting one of 3 explanations: either that the mental burden of EB is similar in milder and more severe subtypes, that patients with more severe EB subtypes have acquired emotional resilience due to the severe impact of living with EB, or that the QOLEB is not appropriate to distinguish between emotions. Such decreased prevalence of emotional burden is also seen with results from a study by Margari et al (13), who found that 80% of EB patients experienced sub-threshold psychiatric symptoms, in particular depression, anxiety, and behaviour disturbances, but that there was no close correlation between these symptoms and the clinical severity of EB (13). Emotional resilience was not explored by Margari et al (13) but has been proposed by Frew et al (3) to explain the lack of consistent quantitative data regarding emotional burden in EB.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies have focused on qualitatively describing the impact of EB on patients' lives (7)(8)(9)(10)(11). Quantitative measurement of HRQoL has been performed using both generic and dermatology-specific instruments in EB patients (6,(12)(13)(14)(15). However, due to ceiling effects and content validity issues of these instruments, the accuracy of the measurements is questionable.…”
mentioning
confidence: 99%
“…A large proportion of persons suffering from the disease consists of children and young adults. The studies are conducted on: -the demand for multi-dimensional care [5], including psychological support [3,4,6]; -the feeling of differentness and exclusion from peer groups [6,7]; -the influence of EB on the quality of life [2,8,9], -the influence of EB on the patient's family [8][9][10].…”
mentioning
confidence: 99%
“…Several studies have investigated this aspect and concluded that general quality of life in EB patients can be poor (Horn et al, 2002;Tabolli et al, 2009;Jeon et al, 2016;Angelis et al, 2016), but data on psychological aspects of EB have been conflicting. Some have reported no manifestation of anxiety and/or depressive symptoms (Fortuna et al, 2016) or other psychiatric disorders (Andreoli et al, 2002), whereas others have found a high prevalence of psychosocial problems and psychiatric symptoms (Margari et al, 2010). …”
Section: Discussionmentioning
confidence: 99%